Sozialbrache - Zur Wirkungsgeschichte eines Begriffs - Freund, Bodo (ERDKUNDE, 1993)
Coined by HARTKE forty years ago, the term social fallow played a special role in German social geography in the development of the indicative approach and the concept of social groups. This paper investigates the long-term development of soil utilization in the classic locations , which served as examples during the early nineteen-fifties; this includes a statement on the justification of the original term. The same concept served to examine other phenomena (like afforestation, special cropping, grass-fallowing) in German agricultural geography. When, in the 'fifties, fallow land also attracted the attention of agricultural sociology, German agricultural geography turned to other social indicators with research declining in the 'sixties, although the phenomenon itself was spreading. Around 1970, fallow suddenly became the theme of a large number of disciplines (botany, agricultural management studies and structural policy, spatial planning, law). During the ' eighties the number of publications declined once more. The fallow phenomenon appears in the landscape as an implication of regional economic and social development. The changing Zeitgeist manifests itself in the varying modes of its everyday awareness as much as in the attention paid by science and planning. Outside the former Federal Republic regionally specific particularities in the occurrence of fallow land, together with national traditions in academic disciplines, have contrived to prevent a general diffusion of the term, although it has been translated into many languages and allows meaningful applications in principle.